2004
DOI: 10.1007/s10735-004-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pretreatment with prolactin on the distribution of immunoreactive beta-endorphin through different ovarian compartments in immature, superovulated rats

Abstract: Beta-endorphin and prolactin (PRL) are natural inhibitors of ovulation via central and peripheral mechanisms, but their possible interactions within the ovary are still unknown. The aims of the present study were to determine the gene expression and the topographic distribution of beta-endorphin, and the possible changes evoked by the pretreatment with PRL on the ovarian beta-endorphin localization in immature, superovulated rats. Prepuberal female Wistar rats weighing 60-70 g were superovulated with 20 IU equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The presence of β-endorphin in the CL of other species -e.g. cows (Ehrenreich et al, 1985), mice (Shaha et al, 1984) and rats (Lolait et al, 1985;Kato et al, 1993;Reis et al, 2004) -has been confirmed. In turn, POMC mRNA was detected in rat CL (Sanders et al, 1990).…”
mentioning
confidence: 87%
“…The presence of β-endorphin in the CL of other species -e.g. cows (Ehrenreich et al, 1985), mice (Shaha et al, 1984) and rats (Lolait et al, 1985;Kato et al, 1993;Reis et al, 2004) -has been confirmed. In turn, POMC mRNA was detected in rat CL (Sanders et al, 1990).…”
mentioning
confidence: 87%